Servo Motor Control System Analysis Using Proteus Simulation - Fathul Ulum; Muhamad Nur Alvyangga Saputro; Mokhammad Syafaat; Kasiyanto (Journal of Creative Power and Ambition (JCPA), 2026)
Servo motors are essential actuator components in the modern mechatronics ecosystem that demands angular positioning precision with minimal error rates. In the control system development phase, direct testing on hardware is often at risk of mechanical damage due to programming errors or current surges. This study aims to conduct an in-depth analysis of the response characteristics of servo motors through a digital simulation approach as a preventive and validative step. The research method applied was a software-based laboratory experiment using the Proteus 8 Professional with an Arduino Uno microcontroller as the central control unit. The main focus of this test lies in the evaluation of the accuracy of the motor angular movement against the pulse width modulation (PWM) provided through the Servo standard library. Data is collected through Virtual Terminal observations and position indicators on virtual servo components. The results show that the Proteus simulation is able to represent the dynamics of angular motion linearly with a 100% accuracy rate to theoretically entered work cycle parameters. The study concludes that the use of virtual modeling is not only effective in minimizing the risk of physical failure.